Niche based relational capability to increase salespeople performance in small and medium enterprises - Udayana, Ida Bagus Nyoman (Business: Theory and Practice, 2022)
The role of salespeople is increasingly important in relation to improving sales performance. Sales may increase if it is supported by reliable, smart and hardworking salesperson. To create a professional salesperson, enterprises need to provide a guidance, for example, in the form of practical training that can support their works. The ability to adapt when interacting with the customers plays a critical role in relation to improving salesperson performance. However, there are inconsistencies in research findings between adaptive sales and salesperson performance. This research was conducted on salesperson in small and medium enterprises. Our sample consists of 300 respondents who lived in the Special Region of Yogyakarta. To obtain proper data, we carried out screening and trimming. The tests include: bias non-response test, logical connection test, and confirmatory factor analysis. This study uses structural equation model. A Sobel test was conducted to test the role of moderating variable. The findings of the research indicate that niche based relational capability was influenced by customers trust orientation, salesperson’s expertise and adaptability when interacting with their customers. The higher customers trust and the more intelligence of salesperson are, it will increase the niche based relational capability. In addition, salesperson’s performance may increase if it is supported by extensive customers relation based on market gaps, trust and salesperson’s intelligence. This research also discusses managerial implication, limitation and the directions for future research.